(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines the effect of solar radiation returning from the Earth’s surface on the solar radiation field in the atmosphere. A calculation method based on Lambert’s law for the intensity of the outgoing radiation flow from the Earth’s surface has been developed, demonstrating its impact on the diffuse and non-diffuse radiation flows in the atmosphere. The results of the calculations provide a theoretical assessment of the illumination level of solar panels by solar radiation flow and allow for the identification of optimal conditions for their stationary installation on the Earth’s surface.